CIS testing system for lensless microfluidic imaging system - Wu, Zhenyu (2016)
With the development of modern technology, CMOS image sensor (CIS) becomes more and more important and has been widely used especially in point-of-care (POC) diagnosis. And the complete blood cell count is one of the most important areas which POC diagnosis has been used. Red blood cells (RBCs), white blood cells (WBCs), and platelets are the three cells which mainly constitute the human bloodstream and platelets have the smallest size among these three cells. In order to capture and distinguish the image of these three cells, a CIS testing system was designed as a testing model for the lensless microfluidic imaging system. So the main objective of this project is to introduce and implement the 3 megapixels CIS testing system of the lensless microfluidic imaging system. Firstly, comparison is made between CMOS and CCD. Then the advantages of CIS is emphasized. And some background information of the photodiode and pixel structure is introduced. Next, CIS chip design and CIS testing system are introduced. And the code and function of Verilog and Matlab are clearly explained. Furthermore, the implementation of the Verilog code operation and image capturing by the CIS testing system are shown in this project. The result is clear and satisfactory so the CIS testing system is proved to be correct and useful. Besides, this project also made a good preparation for future research.